Chemical composition of manganese crusts along the Line Islands archipelago for major and trace elements - Andrew C Aplin; David S Cronan (PANGAEA, 2022)
Thirty Mn crust samples and associated substrates were taken from dredge hauls collected at 16 sites by the Hawaii Institute of Geophysics. They are located along the Line Islands Archipelago between 15°S and 17°N, and from depths between 1150 and 4700 m. Prior to analysis, samples of both crusts and substrates were finely ground and dried over silica gel at room temperature. Following digestion in a mixture of hydrotluoric, nitric and perchloric acids, final solutions were made up in 1 M HCl and anaiysed for Mn, Fe, Ca, Al, Ti, Cu, Ni. Co, Pb and Zn on a Perkin Elmer 5000 atomic absorption spectrophotometer. Most samples were analysed in duplicate. On the basis of replicate analyses and comparison with international nodule standards (analysis by AAS), precisions for all elements were better than 4% and accuracies better than 10% for al1 elements except Al (15%). Foliowing the same procedures, samples were further analysed by inductively coupled plasma spectrophotometry for Be, Sr. Mo, V and Cd in addition to the ten elements analysed for by AAS. Whilst the precision of these analyses was excellent (better than 2%), abundances of some elements were depressed by up to 20% on ICPS with respect to AAS, probably as a result of enhanced rotational interference.